SEJARAH PERTUMBUHAN DAN PERKEMBANGAN TULISAN ARAB - Abd Rahman, Mohd Zaki (Journal of Al-Tamaddun, 2007)
Written characters in Arabic language which is being used now has gone through various changes. At the beginning it seemed to be invented from Phoenician writing that was created by Phoenician who lived in the South of Lubanan during 16th BC. Later, the Phoenician writing was adopted by Nabatean community who lived in Syria and they spread this writing to Arabic Peninsular. After the advent of Islam to Arabic Peninsular, Arabic writing developed tremendously because of the need to record the Quranic verses and Islamic sciences. From here, various efforts were made to develop the Arabic writing capacity, simplify the methodology and spread the Arabic calligraphy. The jawi script used in Malay archipelago is the continuation of Arabic writing with addition of some symbols to complete the needs of pronounciation of Malay words.